UJI EFEKTIVITAS ANTIBAKTERI SEDIAAN SABUN PADAT TRANSPARAN EKSTRAK ETANOL DAUN CABE RAWIT (Capsicum Frutescens L.) TERHADAP BAKTERI Propionibacterium acne - Auliafendri, Novycha; Rila , Etrika Cindy (Universitas Imelda Medan, 2023)
Cayenne pepper leaves (Capsicum frutescens L.) can traditionally be used as an alternative treatment for acne from natural ingredients. This study aims to determine the effectiveness and concentration of the transparent solid soap formulation ethanol extract of cayenne pepper (Capsicum frustescens L.) leaves in inhibiting the growth of acne-causing bacteria (Propionibacterium acne). The method used in this research is experimental. Making cayenne pepper leaf extract (Capsicum Frutescens L.) by maceration method using 96% ethanol then making a transparent solid soap formulation and testing the effectiveness of antibacterial using disc paper diffusion method against Propionibacterium acnes bacteria by measuring the diameter of the inhibition zone for bacterial growth so that it can known Minimum Inhibitory Concentration (MIC). The concentration of Cayenne pepper leaf extract and the transparent solid soap formula used were (FI) 1%; (FII) 2%; (FIII) 3% and blanks (K+) Ranee soap and (K-) extractless soap. Evaluation of the physical quality of transparent solid soap preparations includes: organoleptic test, pH test, foam power test. From the test results, the average transparent solid soap preparation with a concentration of 1% produced an inhibition zone of 10.7 mm, a concentration of 2% produced an inhibition zone of 11.8 mm, and a concentration of 3% produced an inhibition zone of 12.6 mm. Minimum Inhibitory concentration (MIC) which produced the best ethanol extract of cayenne pepper (Capsicum frutescens L.) leaves was found at a concentration of 1% with a Width of Inhibitory Power (LDH) of 10.7 mm. The One Way Anova test obtained a significance value of 0.000 <0.05, so the results were significant, so there were significant differences between treatments. This means that the use of cayenne pepper leaf extract (Capsicum frutescens L.) has an effect on the growth of Propionibacterium acnes bacteria.